Controlling medication nonadherence in chronic illness - Kurniadewi, Komang Sukmaloka; Annisaa', Eva; Thuy, Luu Thi (Innovation in Health for Society, 2021)
Patient adherence during the treatment period must be considered because patient adherence plays an important role in achieving therapeutic success, especially for chronic diseases. Treatment non-adherence is a common and complex problem. Failure to follow a treatment schedule can lead to major health complications, including death. Several interventions are needed to control patient non-adherence. Several interventions can support and improve patient adherence. These include digital interventions, increasing patient knowledge and understanding of the treatment undertaken with counseling, and Drug Information Services (PIO). They provide educational leaflets, digital pillbox reminders, Pill Cards; family support; diaries; keeping treatment commitments. Based on this, it is necessary to have an intervention method in terms of education (educational), behavior (behavior), and attitude (affective) to achieve patient adherence and the success of chronic disease therapy. Keywords: Non-adherence; treatment; chronic disease control; medication; patient care